The Relationship between Board Structure and Performance of Firms Listed at the Nairobi Securities Exchange - Moses Odhiambo Aluoch; Cyrus Iraya Mwangi; Erasmus S. Kaijage; Martin Ogutu (European Scientific Journal, ESJ, 2020)
This study examines the relationship between board structure and performance of firms listed at the Nairobi Securities Exchange. The study is anchored on agency theory, resource dependency theory, transaction cost theory, political theory and a census approach. A population of the study comprising sixty five companies listed at the Nairobi Securities Exchange between 2002 and 2016 were used. Data was extracted from annual reports of listed firms. This study employed longitudinal descriptive research design to determine the relationship. Panel data regression analysis was conducted using the random effects model. The results revealed that gender diversity and occupational expertise had significant effect on Return on Assets, while board independence and board age had significant effect on Tobin’s Q of listed firms in Kenya. On the other hand, board size had an insignificant effect on both Return on Assets and Tobin’s Q. The overall effect of board structure on Returns on Assets and Tobin’s Q was significant. The study concluded that various board structure mechanisms except board size have significant effect on performance of listed firms in Kenya, and the overall board structure had significant effect on performance of listed firms. The study recommended that management should incorporate board structure mechanisms to enhance performance of firms and regulatory authorities should review the current board structure variables to make them more relevant to improve performance of listed firms in Kenya.